Pelatihan Pembuatan Pupuk Organik Cair (POC) Berbahan Kulit Pepaya dan Hama Keong Mas (Kul) Sebagai Upaya Minimize Cost Pada Petani Di Desa Gading, Kabupaten Pasuruan. - Siska, Adela Silviana; K, Alda Sylvia; Archadea, Cawla; Desilva, Melati Putri; Putri, Melinda Aprilia; Rizkiyah, Noor (Ikatan Da'i Indonesia, 2024)
The training program on making Liquid Organic Fertilizer (POC) in Gading Village, Pasuruan District, East Java, is a response to two major challenges: the declining allocation of subsidized fertilizers and the infestation of carp snails in rice crops. This initiative aims to turn threats into opportunities by utilizing carp snails and papaya peel waste as raw materials for POC. Through collaboration between PT Lembaga Sahabat Petani and UPN